Biological Response to Sintered Titanium in Left Ventricular Assist Devices: Pseudoneointima, Neointima, and Pannus. Issue 1 (31st May 2022) - He, Wenxuan; Butcher, Jonathan T.; Rowlands, Grant W.; Antaki, James F.
Abstract : Titanium alloys have traditionally been used in blood-contacting cardiovascular devices, including left ventricular assist devices (LVADs). However, titanium surfaces are susceptible to adverse coagulation, leading to thrombogenesis and stroke. To improve hemocompatibility, LVAD manufacturers introduced powder sintering on blood-wetted surfaces in the 1980s to induce endothelialization. This technique has been employed in multiple contemporary LVADs on the pump housing, as well as the interior and exterior of the inflow cannula. Despite the wide adoption of sintered titanium, reported biologic response over the past several decades has been highly variable and apparently unpredictable—including combinations of neointima, pseudoneoimtima, thrombus, and pannus. We present a history of sintered titanium used in LVAD, a review of accumulated clinical outcomes, and a synopsis of gross appearance and composition of various depositions found clinically and in animal studies, which is unfortunately confounded by the variability and inconsistency in terminology. Therefore, this review endeavors to introduce a unified taxonomy to harmonize published observations of biologic response to sintered titanium in LVADs. From these data, we are able to deduce the natural history of the biologic response to sintered titanium, toward development of a deterministic model of the genesis of a hemocompatible neointima.